Analyzing and Improving Data Quality - Buccella, Agustina
Data quality is a research area strongly investigated during the 90’s. However, few companies in Argentina apply data quality methodologies or tools during the analysis, design or implementation phases of software development process. Developers generally use techniques to design systems such as UML without considering mechanisms for future data quality problems. In this work we propose a methodology in which the data quality is an essential part of the whole software development process. Early design decisions on data quality strongly impact on the system. Our methodology defines a set of practices to be applied on the software life cycle. In addition these practices act as a means to evaluate if systems already running fulfill with minimal data quality requirements.